Bilateral Ascending Uterine Artery Ligation vs. Tourniquet Use for Hemostasis in Cesarean Myomectomy: A Comparison - Sapmaz, Ekrem; Çelik, Hüsnü; Altungül, Aygen (Journal of Reproductive Medicine, Inc., 2003)
OBJECTIVE: To comparatively investigate the effects of using bilateral ascending uterine artery ligation and tourniquet use on intraoperative and postoperative blood loss during myomectomy in cesarean cases. STUDY DESIGN: A total of 70 pregnant women diagnosed with myomas in the prenatal period were included in this randomized, prospective study. They were admitted to our department during the study period. Fifty-two patients who underwent cesarean myomectomy were randomly divided into 2 equal groups. In the first group bilateral ascending uterine artery ligation and myomectomy were performed after lower uterine segment transverse cesarean section. The second group served as the control group; myomectomy was performed with a tourniquet. For statistical analysis, Mann Whitney U, ?2 and Wilcoxon Rank tests were used. Spearman correlation analysis (rs, n, p) was used for analysis of correlation between the duration of the myomectomy operation and blood loss and number of enucleated myoma nuclei during myomectomy. RESULTS: Total intraoperative blood loss, total operation duration, number of enucleated myoma nuclei (Mann Whitney U test) and febrile morbidity (?2 test) were similar in the 2 groups (P > .05). A significant positive correlation was established between the duration of the myomectomy operation and loss of blood and number of enucleated myoma nuclei during myomectomy (rs =.9, n=52, P=.000). Urgent laparotomy and bilateral internal iliac artery ligation had to be performed in 1 patient in the tourniquet group who had a postoperative hemorrhage. CONCLUSION: Despite the fact that bilateral ascending uterine artery ligation and tourniquet use had similar outcomes with regard to intraoperative blood loss in cesarean myomectomy cases, the efficacy of ligation on blood loss in the postoperative period continues owning to its permanence. The tourniquet method is not effective in the postoperative period since the tourniquet is removed at the end of the operation. Therefore, bilateral ascending uterine artery ligation may be preferable in cesarean myomectomy cases.
Keywords: Cesarean section; Myoma; Myomectomy; Tourniquets; Uterine artery ligation